2019
DOI: 10.1016/j.joms.2018.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Associated Injuries Are Frequent and Severe Among Geriatric Patients With Zygomatico-Orbital Fractures

Abstract: Purpose: Associated injuries (AIs) are hypothesized to be frequent in geriatric zygomatico-orbital (ZMO) fractures. The study aim was to determine the relation between ZMO fractures and AIs in geriatric patients compared with younger adult patients. Patients and Methods: A retrospective case-and-control study was carried out on geriatric patients at least 65 years of age (n = 93) and younger adult patients 20 to 30 years of age (n = 68) diagnosed with pure unilateral ZMO fractures. The main exposure was age, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
3
6
0
Order By: Relevance
“…A single institution retrospective case and control study that evaluated the relationship between associated injuries, like brain injury, and geriatric zygomatico-orbital fractures in elderly (n = 93) and younger adults (n = 68) found that brain injuries were significantly more frequent ( p < 0.001) in the geriatric group (over 65 years old) than in the control group (20–30years of age). 26 Skull fractures occur when a significant force (greater than mechanical integrity of the calvarium) strikes the head. These were seen more commonly in younger adults coinciding with higher velocity mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…A single institution retrospective case and control study that evaluated the relationship between associated injuries, like brain injury, and geriatric zygomatico-orbital fractures in elderly (n = 93) and younger adults (n = 68) found that brain injuries were significantly more frequent ( p < 0.001) in the geriatric group (over 65 years old) than in the control group (20–30years of age). 26 Skull fractures occur when a significant force (greater than mechanical integrity of the calvarium) strikes the head. These were seen more commonly in younger adults coinciding with higher velocity mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The literature indicates that most serious maxillofacial fractures are caused by road traffic accidents. [30][31][32][33] The proportion of maxillofacial injuries caused by traffic accident decreased greatly in 2020, because the implementation of traffic control measures had greatly reduced the incidence of traffic accidents. In this study, injuries that involve only soft tissue or teeth accounted for the majority of injuries during the epidemic, which was in connection with the overwhelming majority of falls.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that falling due to violence was the most significant injury mechanism that independently increased the risk of associated injuries. Falling as a major risk factor was not an altogether surprising finding; a higher incidence of associated injuries was observed in a study on elderly patients with zygomatico-maxillary-orbital fractures 19 , and falls are known to be a major aetiological factor for facial fractures in the elderly 20 . Although these factors can affect assaults individually, a possible predisposing factor could be al- The patient population N = 840; % is the column percentage (i.e., the percentage of patients within each group with the given characteristic); '% of n' is the row percentage (i.e., the distribution of patients with the given characteristic between the two groups).…”
Section: Discussionmentioning
confidence: 97%